Robotic eyes that express personality. (18th April 2019) - Luo, Liangyi; Koyama, Naoki; Ogawa, Kohei; Ishiguro, Hiroshi
ABSTRACT: We create robots to help people, and we believe that our robots can be more helpful if they look and behave as humans do. People usually prefer help from those whom they like. Some people can be likeable for their personality. A robot, especially an android, may become likeable too if it expresses likeable personality. A robot, or at least an android, needs the ability to express personality such that it can become more likeable, that its help can be more readily accepted. As the first step, we have investigated how the robotic eyes of an android may express personality. Humans have expressive eyes. We postulate that human eyes express personality. We experimented to see whether our test subjects could perceive distinct personalities in an android we programmed to imitate the eye movements of two people. The result showed that the android did express distinct personalities, but not without limitations. GRAPHICAL ABSTRACT: